Integral problem.(arc length)

my problem is to find the arc length of $$y=e^x$$ between 0 and 1

what i've got is $$\int_{0}^{1} \sqrt{1+(e^x)^2}dx$$ which i then substitute $$u=e^x$$ giving $$\int_{1}^{e} \frac{\sqrt{1+u^2}}{u^2}u du$$ which i then sub in v=$$\sqrt{1+u^2}$$ giving $$\int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v^2}{(v^2-1)^2} dv = \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v}{(v^2-1)} dv = \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v}{(v-1)(v+1)} dv$$ which then needs to be integrated using partial fractions, and this is where i run into problems

i get $$\frac{1}{2} \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{1}{v-1}+\frac{1}{v+1}dv$$ which results in my getting an answer of 1.

the book on the other hand gets $$\int_{\sqrt{2}}^{\sqrt{1+e^2}}1+ \frac{\frac{1}{2}}{v-1}-\frac{\frac{1}{2}}{v+1}dv$$ but i cant see how they got the 1, or the negative sign on the second fraction

Related Introductory Physics Homework Help News on Phys.org

dextercioby

Homework Helper
my problem is to find the arc length of $$y=e^x$$ between 0 and 1

what i've got is $$\int_{0}^{1} \sqrt{1+(e^x)^2}dx$$ which i then substitute $$u=e^x$$ giving $$\int_{1}^{e} \frac{\sqrt{1+u^2}}{u^2}u du$$ which i then sub in v=$$\sqrt{1+u^2}$$ giving $$\int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v^2}{(v^2-1)^2} dv = \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v}{(v^2-1)} dv = \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v}{(v-1)(v+1)} dv$$ which then needs to be integrated using partial fractions, and this is where i run into problems

i get $$\frac{1}{2} \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{1}{v-1}+\frac{1}{v+1}dv$$ which results in my getting an answer of 1.

the book on the other hand gets $$\int_{\sqrt{2}}^{\sqrt{1+e^2}}1+ \frac{\frac{1}{2}}{v-1}-\frac{\frac{1}{2}}{v+1}dv$$ but i cant see how they got the 1, or the negative sign on the second fraction

I think you have a problem there.EDIT;It doesn't work.Well,when u got rid of the square in the variable "v".

Daniel.

arildno

Homework Helper
Gold Member
Dearly Missed
my problem is to find the arc length of $$y=e^x$$ between 0 and 1

what i've got is $$\int_{0}^{1} \sqrt{1+(e^x)^2}dx$$ which i then substitute $$u=e^x$$ giving $$\int_{1}^{e} \frac{\sqrt{1+u^2}}{u^2}u du$$ which i then sub in v=$$\sqrt{1+u^2}$$ giving $$\int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v^2}{(v^2-1)^2} dv = \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v}{(v^2-1)} dv = \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v}{(v-1)(v+1)} dv$$ which then needs to be integrated using partial fractions, and this is where i run into problems

i get $$\frac{1}{2} \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{1}{v-1}+\frac{1}{v+1}dv$$ which results in my getting an answer of 1.

the book on the other hand gets $$\int_{\sqrt{2}}^{\sqrt{1+e^2}}1+ \frac{\frac{1}{2}}{v-1}-\frac{\frac{1}{2}}{v+1}dv$$ but i cant see how they got the 1, or the negative sign on the second fraction
This equality is wrong:
$$\int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v^2}{(v^2-1)^2} dv = \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v}{(v^2-1)} dv$$

yeah, i am seeing that...the book jumps from $$\int_{1}^{e} \frac{\sqrt{1+u^2}}{u^2}u du$$ to $$\int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v}{(v^2-1)} dv$$ and (without checking) i figured $$\frac{x^2}{y^2}=\frac{x}{y}$$ my mistake. now i'm really confused, because i see how they get $$\int_{1}^{e} \frac{\sqrt{1+u^2}}{u^2}u du$$ but dont know where to go from there now.

dextercioby

Homework Helper
$$\int_{1}^{e} \sqrt{\frac{1}{u^{2}}+1} \ du$$

Make the sub.

$$\frac{1}{u} =\sinh t$$

Daniel.

GCT

Homework Helper
From here, $$\int_{1}^{e} \frac{\sqrt{1+u^2}}{u} du$$[/quote]

try the substitution $$u=1/t$$

can anyone see what the book did(i would like to get it solved the same way they did it.) up to the point where it subs in v i can see what they did, but when i sub in v i get $$\int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v^2}{(v^2-1)^2} dv$$ and dont know how they got the roots of it.
and even then i dont see how they got the 1 and the negative in the partial fraction.

dextercioby

Homework Helper
GCT,you're not being original... Daniel.

Homework Helper

OlderDan

Homework Helper
yeah, i am seeing that...the book jumps from $$\int_{1}^{e} \frac{\sqrt{1+u^2}}{u^2}u du$$ to $$\int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v}{(v^2-1)} dv$$ and (without checking) i figured $$\frac{x^2}{y^2}=\frac{x}{y}$$ my mistake. now i'm really confused, because i see how they get $$\int_{1}^{e} \frac{\sqrt{1+u^2}}{u^2}u du$$ but dont know where to go from there now.
If the book makes that jump, it is a typographical error. It should be

$$\int_{1}^{e} \frac{\sqrt{1+u^2}}{u^2}u du = \int_{\sqrt{2}}^{\sqrt{1+e^2}} \frac{v^2}{(v^2-1)} dv$$

And their result follows. The u in this equation is just the original y, and v is as you defined it. Taking it from the top

$$y = e^x$$

$$dy = e^x dx = ydx \Rightarrow dx = \frac{{dy}}{y}$$

$$ds = \sqrt {dx^2 + dy^2 } = \left( {\sqrt {\frac{1}{{y^2 }} + 1} } \right)dy = \frac{{\sqrt {1 + y^2 } }}{y}dy\left( { = \frac{{\sqrt {1 + y^2 } }}{{y^2 }}ydy} \right)$$

$$v = \sqrt {1 + y^2 } \Rightarrow dv = \frac{1}{{2v}}2ydy = \frac{{ydy}}{v} \Rightarrow dy = \frac{v}{y}dv$$

$$v^2 = 1 + y^2 \Rightarrow y^2 = v^2 - 1$$

$$ds = \frac{{\sqrt {1 + y^2 } }}{y}dy = \frac{v}{y} \cdot \frac{v}{y}dv = \frac{{v^2 }}{{y^2 }}dv = \frac{{v^2 }}{{v^2 - 1}}dv$$

$$ds = \left( {1 + \frac{1}{{v^2 - 1}}} \right)dv = \left( {1 + \frac{1}{{v - 1}} \cdot \frac{1}{{v + 1}}} \right)dv = \left( {1 + \frac{{\frac{1}{2}}}{{v - 1}} - \frac{{\frac{1}{2}}}{{v + 1}}} \right)dv$$

Physics Forums Values

We Value Quality
• Topics based on mainstream science
• Proper English grammar and spelling
We Value Civility
• Positive and compassionate attitudes
• Patience while debating
We Value Productivity
• Disciplined to remain on-topic
• Recognition of own weaknesses
• Solo and co-op problem solving